Sulfonic acid-functionalized PCP(Cr) catalysts with Cr3+ and –SO3H sites for 5-ethoxymethylfurfural production from glucose. Issue 54 (19th October 2021) - Zhang, Luxin; Liu, Yuting; Sun, Ruijun; Yi, Simin
Abstract : The PCP(Cr)-BA catalysts featured porous morphology and dual Cr 3+ and –SO3 H sites, which enabled the cascade conversion of glucose to EMF. In addition, the as-prepared catalyst exhibited a high stability in the current catalytic system. Abstract : 5-Ethoxymethylfurfural (EMF) has been identified as a potential biofuel and fuel additive, for which the production from glucose (the most abundant and inexpensive monosaccharide) in a one-step process would be highly desirable. Here, the synthesis of sulfonic acid-functionalized porous coordination polymers (PCPs) and their application as catalysts for EMF synthesis are reported. PCP(Cr)-BA (PCP material with Cr 3+ ions and H2 BDC-SO3 H linkers) and PCP(Cr)-NA (PCP material with Cr 3+ ions and H2 NDC(SO3 H)2 linkers) materials containing both Cr 3+ sites and Brønsted-acidic –SO3 H sites were prepared. The morphology, pore structure, acidity, chemical composition, and thermal stability of the two functionalized PCP(Cr) catalysts were analyzed by systematic characterization. The catalysts featured a porous morphology and dual Cr 3+ and –SO3 H sites, which enabled the cascade conversion of glucose to EMF. PCP(Cr)-BA exhibited higher performance than PCP(Cr)-NA with an EMF yield of 23.1% in the conversion of glucose at 140 °C after 22 h in an ethanol/water system. In addition, the as-prepared catalyst exhibited a high stability in the current catalytic system for EMF production from glucose with a constant catalytic activity in a four-run recycling test without an intermediate regeneration step.